2018
DOI: 10.1038/s41598-018-36428-7
|View full text |Cite
|
Sign up to set email alerts
|

Relation between mitochondrial DNA hyperdiversity, mutation rate and mitochondrial genome evolution in Melarhaphe neritoides (Gastropoda: Littorinidae) and other Caenogastropoda

Abstract: Mitochondrial DNA hyperdiversity is primarily caused by high mutation rates (µ) and has potential implications for mitogenome architecture and evolution. In the hyperdiverse mtDNA of Melarhaphe neritoides (Gastropoda: Littorinidae), high mutational pressure generates unusually large amounts of synonymous variation, which is expected to (1) promote changes in synonymous codon usage, (2) reflect selection at synonymous sites, (3) increase mtDNA recombination and gene rearrangement, and (4) be correlated with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 68 publications
8
31
1
Order By: Relevance
“…It is also worth noticing that all currently available species of gen. Gammarus have the same conserved gene order in their mitogenomes, whereas the majority of Baikalian species in both lineages possess different types of gene rearrangements and additional tRNA gene copies (Romanova et al, 2016;. Our analysis supports an opinion about the linkage of high evolutionary rate and gene rearrangements in mitogenomes (Shao et al, 2003;Fourdrilis et al, 2018).…”
Section: Resultssupporting
confidence: 78%
“…It is also worth noticing that all currently available species of gen. Gammarus have the same conserved gene order in their mitogenomes, whereas the majority of Baikalian species in both lineages possess different types of gene rearrangements and additional tRNA gene copies (Romanova et al, 2016;. Our analysis supports an opinion about the linkage of high evolutionary rate and gene rearrangements in mitogenomes (Shao et al, 2003;Fourdrilis et al, 2018).…”
Section: Resultssupporting
confidence: 78%
“…In our study, it was found that A+T base content is higher than G+C base content, which is consistent with other reports that A+T base content is higher in the mitochondrial genome in animals (Fourdrilis et al 2018). A total of 49 mtDNA CR haplotypes were analyzed and 39 haplotypes were private.…”
Section: Genetic Diversitysupporting
confidence: 92%
“…Amphipod species with currently sequenced mt genomes belong to different taxa and occupy different ecological niches, making it possible to suggest whether mt gene order rearrangements correlate with ecological features of species, their time of lineage divergence or life-history traits, etc. There was shown a positive correlation of the rate of gene rearrangements with the level of nucleotide substitutions in their protein-coding genes (Shao et al, 2003;Fourdrilis et al, 2018). We also recently demonstrated the significant increase in mutation rate in both lineages of Baikalian amphipods in comparison to species from gen. Gammarus (Romanova and Sherbakov, 2019).…”
Section: Introductionmentioning
confidence: 62%